Development of certain new 2-substituted-quinazolin-4-yl-aminobenzenesulfonamide as potential antitumor agents - Alafeefy, Ahmed Mahmoud; Ahmad, Rehan; Abdulla, Maha; Eldehna, Wagdy M.; Al-Tamimi, Abdul-Malek S.; Abdel-Aziz, Hatem A.; Al-Obaid, Omar; Carta, Fabrizio; Al-Kahtani, Abdulla A.; Supuran, Claudiu T. (2016)
Carbonic anhydrases (CA I, II, IX and XII) are known to be highly expressed in various human malignancies. CA IX is overexpressed in colorectal cancer specifically in hereditary nonpolyposis colorectal cancer. Inhibition of CA activity by small molecular CA inhibitor like sulphonamides, sulphonamide derivative (SU.D2) or HIF1a inhibitor Chetomin leads to inhibition of tumorigenesis. Eighteen new quinazolin- 4-sulfonamide derivatives were prepared and characterized by means of IR, NMR and mass spectra. Certain selected derivatives were tested for their ability to inhibit four isoforms of the metalloemzyme CA, namely, CA I, CA II, CA IX and CA XII. Compound 3c was found to be highly effective in inhibiting the cancer cell proliferation. 3c decreased cell viability of human HT-29 cells in dose and time dependent manner and with IC50 of 5.45 mM. Moreover, it was tested on metastatic colon cancer cell SW- 620 where it was found to be equally effective on human SW-620 cells. This novel compound inhibited the CA IX and CA XII protein expression in HT-29 cells without affecting CA I and CA II expression. These findings indicate that 3c inhibits cellular proliferation in two human colon cancer cells by specifically targeting the CA IX and CA XII expression.